Pengaruh Atribut Produk, Iklan, Harga, Dan Kebutuhan Mencari Variasi Terhadap Keputusan Perpindahan Merek Ke Yamaha NMAX Di Semarang Selatan - Nurul Huda; Nurchayati Nurchayati (Serat Acitya, 2018)
This study aims to determine the effect of product attributes, advertising, prices, and the need to find variations on the brand switching decision to Yamaha NMAX in the area of South Semarang. The population in this study is all consumers who bought Yamaha NMAX motorcycles in South Semarang in 2017. The sample size used as many as 100 respondents, and sampling techniques used quota sampling. Data collection techniques using questionnaires, and data analysis used is multiple linear regression analysis.The result of equation obtained from multiple linear regression analysis shows that product attributes, advertising, price, and need for variation have positive effect on brand switching decision. Coefficient of determination 0,796, meaning that product attribute, advertising, price, and need to find variation can explain variation of variable brand switching decision is 79,6%. F test results obtained value 0.000 <0.05, that the resulting regression model is fit, so the regression model is significant and feasible to use. The result of hypothesis test with t statistic test show that (1) product attribute have positive and significant effect to brand switching decision, (2) advertising have positive and significant effect to brand switching decision, (3) price have positive and significant influence to brand switching decision, and (4) the need to track variations has a positive and significant impact on brand switching decision.